Association of salivary gland hypofunction with diabetes mellitus and drugs among the elderly in Karachi, Pakistan. Issue 2 (30th January 2016) - Lone, Muneeb Ahmed; Shaikh, Sameer; Lone, Maham Muneeb; Afaq, Ashar; Lone, Mohid Abrar
Abstract: Aim: Studies from Pakistan on salivary dysfunction are lacking, and the Pakistani elderly population is rapidly growing. Among the most common problems in the elderly that could have a deleterious impact on their quality of life are salivary gland hypofunction (SGH), diabetes mellitus (DM), and the intake of drugs with adverse effects on salivary function. In the present study, we aimed to find the association of SGH with DM and drugs among the elderly in Karachi, Pakistan. Methods: The inclusion criterion was affirmative answers to a series of standardized questions related to the symptoms of dry mouth. A total of 110 individuals were selected from a convenience sample of 200 people aged between 60 and 70 years. Diabetes, drug use, and SGH in the participants were determined by detailed medical and drug history, clinical examination, and sialometry. Results: Similar to their international counterparts, the majority of the study participants demonstrated objective evidence of SGH. More importantly SGH was found to be statistically significant with respect to DM and medication ( P < 0.05). For participants on medication, the minimum and maximum salivary flow rates were found to be 0.09 mL/min and 0.3 ml/min, respectively, whereas the minimum and maximum salivary flow rates in diabetic participants were 0.01 mL/min and 0.09 mL/min, respectively. Conclusion: In the present study, the majority of elderly participants whose presenting complaint was oral dryness was found to have objective evidence of SGH, with a statistically‐significant association with DM and drugs.